Assessment of respiratory muscle strength in children according to the classification of body mass index - da Rosa, George Jung (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE: To assess and compare the respiratory muscle strength among eutrophic, overweight and obese school children, as well as to identify anthropometric and respiratory variables related to the results. METHODS: Cross-sectional survey with healthy schoolchildren aged 7-9 years old, divided into three groups: Normal weight, Overweight and Obese. The International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire was applied. The body mass index (BMI) was evaluated, as well as the forced expiratory volume in one second (FEV(1)) with a portable digital device. The maximal inspiratory and expiratory pressures (MIP and MEP) were measured by a digital manometer. Comparisons between the groups were made by Kruskal-Wallis test. Spearman's correlation coefficient was used to analyze the correlations among the variables. RESULTS: MIP of eutrophic school children was higher than MIP found in overweight (p=0.043) and obese (p=0.013) children. MIP was correlated with BMI percentile and weight classification (r=-0.214 and r=-0.256) and MEP was correlated with height (r=0.328). Both pressures showed strong correlation with each other in all analyses (r≥0.773), and less correlation with FEV(1) (MIP - r=0.362 and MEP - r=0.494). FEV(1) correlated with MEP in all groups (r: 0.429 - 0.569) and with MIP in Obese Group (r=0.565). Age was correlated with FEV(1) (r=0.578), MIP (r=0.281) and MEP (r=0.328). CONCLUSIONS: Overweight and obese children showed lower MIP values, compared to eutrophic ones. The findings point to the influence of anthropometric variables on respiratory muscle strength in children.